More on quadratics

Why does the general method Factorising quadratics, work? We are trying to factorise a general quadratic ax²+bx+c [1] into the form (dx+e)(fx+g). Multiplying this out gives: dx(fx+g)+e(fx+g) [2] dfx²+dgx+efx+eg [3] dfx²+(dg+ef)x+eg [4] If a = df, b = dg+ef and c = eg, then equation [1] is same as equation [4]. So ac can be... Continue Reading →

Factorising quadratics

When factorising quadratics of the form x²+bx+c, the usual procedure is to write it like this: (x+..)(x+..) and then think of 2 numbers which multiply together to give c and add up to give b. So, for example: x²+x-12 factorises to (x+4)(x-3), because 4 * -3 = -12 and 4-3=1. Possible combinations which multiply together... Continue Reading →

Powered by WordPress.com.

Up ↑